Effectiveness of an Individual Cognitive-Behavioral Intervention for Serious, Young Male Violent Offenders: Randomized Controlled Study With Twenty-Four-Month Follow-Up - Lardén, Martin; Högström, Jens; Långström, Niklas (Frontiers in Psychiatry, 2021)
Background: Psychological recidivism-reducing interventions with serious, young violent offenders in residential care have unsatisfactory effects. We tested if a complementary individual cognitive behavioral therapy (iCBT) intervention focusing problem-solving, cognitive self-control and relapse prevention reduces criminal recidivism beyond usual institutional care encompassing interventions such as social skills training and prosocial modelling (treatment-as-usual; TAU). Method: We consecutively approached 115 eligible serious, male violent crime offenders in five residential treatment homes run by the Swedish National Board of Institutional Care. Eighty-one (70%) 16–21-year-old youth at medium-high violent recidivism risk were included and randomized to an individualized 15–20-session CBT intervention plus TAU (n=38) or to TAU-only (n=43), 4–6 months before release to the community. Participants were assessed pre- and post-treatment, at 12 months (self-reported aggressive behavior, reconvictions) and 24 months (reconvictions) after release. Intent-to-treat analyses were applied. Results: The violent reconviction rate was slightly higher for iCBT+TAU vs. TAU-only youth at 12 months (34% vs. 23%, d=0.30, 95% CI: -0.24–0.84) and 24 months following release (50% vs. 40%, d=0.23, 95% CI: -0.25–0.72), but neither of these differences were significant. Cox regression modelling also suggested non-significantly, negligibly to slightly more violent and any criminal recidivism in iCBT+TAU vs. TAU-only youth during the entire follow-up. Further, we found no significant between-group differences in conduct problems, aggression, and antisocial cognitions, although both iCBT+TAU and TAU-only participants reported small to large within-group reductions across outcome measures at post-treatment. Finally, the 12-month follow-up suggested marginally more DSM-5 Conduct Disorder symptoms of “aggression to people and animals” in iCBT+TAU vs. TAU-only youth (d=0.10, 95% CI: -0.40–0.60) although this difference was not significant. Conclusion: We found no additive effect of individual CBT beyond group-based TAU in residential psychological treatment for serious, young male violent offenders. Limited sample size and substantial treatment dropout reduced the robustness of intent-to-treat effect estimates. We discuss the possible impact of treatment dose and integrity, participant retention, and TAU quality.